Traditional Thai Compress Therapy for Pain Relief and Enhanced Physical Activity in Patients with Rheumatoid Arthritis: A Randomized Controlled Trial - Beti Kristinawati; Nyofan Wahyu Mardana; Nove Wiand Dwi Wijayanti; Nurhanan Baikadem (Tehran University of Medical Sciences, 2024)
Rheumatoid arthritis (RA) is a persistent inflammatory condition that impacts the joints, resulting in sensations of discomfort, reduced mobility, and localized edema. This study investigates the efficacy of Traditional Thai Compress therapy in mitigating pain and enhancing physical functioning among persons diagnosed with RA. The study was conducted as a randomized controlled trial (RCT). There are the groups where the participants were randomly assigned-each group comprises 141 individuals. To address the possibility of bias and to uphold the objectivity in the research investigation, blinding methods were employed for both therapists and assessors. This study used three questionnaires: the Demographic Questionnaire, the Visual Analogue Scale (VAS) for pain assessment, and the Health Assessment Questionnaire Disability Index (HAQ-DI) for evaluating physical activity levels. After one month of implementing the therapy, there were no notable differences observed in the control group. Additionally, it is worth noting that the intervention group displayed a difference that has been determined to be significant from a statistical standpoint in the level of pain and physical activity ratings among all categories (p < 0.001). The Traditional Thai Compress has been found to provide substantial empirical data that supports its therapeutic efficacy in reducing pain and enhancing physical functionality in individuals diagnosed with RA.